2018
DOI: 10.1002/cche.10041
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between Falling Number, α‐amylase activity, milling, cookie, and sponge cake quality of soft white wheat

Abstract: Background and objectives: Falling Number (FN) in wheat is an important quality predictor and carries a significant economic impact. Lower FN is associated with higher a-amylase activity and poorer soft wheat end-use quality, especially sponge cake. The objective was to examine wheat samples with a range of FN between 70 > 300 s for a-amylase activity and sponge cake quality. Findings: Falling Number was moderately well correlated with a-amylase activity. Stirring Number, an alternative to FN, was poorly corre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
40
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(46 citation statements)
references
References 26 publications
2
40
0
1
Order By: Relevance
“…In this study there was a clear absence of correlation between LMA related eFN and any of the baking quality traits analyzed. Interestingly a recent study also highlighted the weak correlation between low FN in soft wheat and Japanese sponge cake volume ( Kiszonas et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…In this study there was a clear absence of correlation between LMA related eFN and any of the baking quality traits analyzed. Interestingly a recent study also highlighted the weak correlation between low FN in soft wheat and Japanese sponge cake volume ( Kiszonas et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…When FN is further decreased to 100 s, the volume is decreased by about 15% (Finney, Natsuaki, Bolte, Mathewson, & Pomeranz, ; Kaldy & Rubenthaler, ). However, a recent study with a larger sample size of 55 soft white wheat samples, found that the correlation between FNs and sponge cake volume is low, with a coefficient of determination ( R 2 ) value below 0.42 (Kiszonas, Engle, Pierantoni, & Morris, ). This contradictory result indicates that using FN to evaluate wheat quality for making sponge cake or similar products needs further investigation.…”
Section: Falling Numbermentioning
confidence: 99%
“…These two samples were (i) laboratory sprouted to a modest level (18 hr) and (ii) had experienced environmental conditions that induced both LMA and PHS. Consequently, these two kits were not successful at detecting elevated levels of wheat α‐amylase associated with reduced flour quality (Kiszonas et al., ). The AMY2 kit, however, successfully detected increased levels of α‐amylase in both samples known to have greater α‐amylase activity.…”
Section: Resultsmentioning
confidence: 99%
“…When the germination process begins after crop physiological maturity but before harvest, the phenomenon is known as preharvest sprouting (PHS). PHS is associated with reduced grain and flour quality (Finney, Natsuaki, Bolte, Mathewson, & Pomeranz, ; Greenaway, ; Kiszonas, Engle, Pierantoni, & Morris, ), and various means have been developed to assess the extent of damage due to PHS. One of the most widely accepted methods is the Hagberg‐Perten Falling Number (FN) instrument (Hagberg, , ; Perten, ) (AACCI, Approved Method 56‐81.03).…”
Section: Introductionmentioning
confidence: 99%